Violence against children in Latin America and Caribbean countries: a comprehensive review of national health sector efforts in prevention and response - Andrea L. Wirtz; Carmen Alvarez; Alessandra C. Guedes; Luisa Brumana; Cecilie Modvar; Nancy Glass (BMC, 2016)
Abstract Background Violence against children (VAC) remains a global problem. The health sector has an opportunity and responsibility to be part of the multi-sector collaboration to prevent and respond to VAC. This review aimed to assess the health sector's response to VAC among Latin American & Caribbean (LAC) countries, particularly as it relates to physical violence, sexual violence, and neglect. Method National protocols for the identification and provision of health care to child survivors of violence, abuse and neglect were solicited in partnership with UNICEF and PAHO/WHO country offices within the LAC region. A parallel systematic review was undertaken in January 2015 to review studies published in the last 10 years that describe the regional health sector response to VAC. Results We obtained health sectors guidelines/protocols related to VAC from 22 of 43 (51 %) countries and reviewed 97 published articles/reports that met the review inclusion criteria. Country protocols were presented in Spanish (n = 12), Portuguese (n = 1), and English (n = 9). Thematic areas of country protocols included: 1) identifying signs and symptoms of VAC, 2) providing patient-centered care to the victim, and 3) immediate treatment of injuries related to VAC. The systematic review revealed that health professionals are often unaware of national protocols and lack training, resources, and support to respond to cases of VAC. Further, there is limited coordination between health and social protection services. Conclusions VAC remains an international, public health priority. Health professionals are well-positioned to identify, treat and refer cases of VAC to appropriate institutions and community-based partners. However, poor protocol dissemination and training, limited infrastructure, and inadequate human resources challenge adherence to VAC guidelines.